2008
DOI: 10.1097/bot.0b013e318169ef08
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Fracture Morphology of the Posteromedial Fragment in Bicondylar Tibial Plateau Fracture Patterns

Abstract: A posteromedial fragment was observed in nearly one third of the bicondylar plateau fractures evaluated. The morphologic features of this fragment may have clinical implications when using currently available laterally applied fixed-angle screw/plate implants to stabilize these injuries. Alternate or supplementary fixation methods may be required when managing this injury pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
163
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 30 publications
8
163
0
9
Order By: Relevance
“…We note that the morphological characteristics of the complex bicondylar four-quadrant tibial plateau fractures follow a regular pattern, which was also described by others [8][9][10][11][12]. The concave medial plateau is usually split into two large fragments (posteromedial and anteromedial) without articular depression, while the convex lateral plateau is split-depressed into various degrees of multi-fragments with broadening of the lateral compartment (anterolateral and posterolateral).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We note that the morphological characteristics of the complex bicondylar four-quadrant tibial plateau fractures follow a regular pattern, which was also described by others [8][9][10][11][12]. The concave medial plateau is usually split into two large fragments (posteromedial and anteromedial) without articular depression, while the convex lateral plateau is split-depressed into various degrees of multi-fragments with broadening of the lateral compartment (anterolateral and posterolateral).…”
Section: Discussionmentioning
confidence: 66%
“…Chang et al [6,7] classified the tibial articular plateau into four-quadrants, and the fractures are categorized with an isolated single quadrant (anteromedial, anterolateral, posteromedial, and posterolateral) and different combinations of 2, 3 and 4 quadrants. The fracture on each quadrant may have unique characteristics [8][9][10][11][12] as well as require related incision or treatment protocols [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Barie et al have shown the presence of these fragments in 33% of tibial plateau fractures. 5 Hackl et al found that 40% of the fractures classified with plain AP radiographs using Schatzker classification have to be changed after doing Computed Tomography (CT). 10 Historically these fractures have been treated with single midline incision which was associated with high wound complication rate and secondary loss of alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Barie et al have shown the presence of these fragments in 33% of tibial plateau fractures. 5 Several biomechanical studies have proved that fixation of these fragment is necessary to prevent secondary loss of alignment like varus collapse. 4 We have tried to assess the outcome of these fractures using ORIF with locking or buttress plate through Lobenhoffer approach.…”
Section: Introductionmentioning
confidence: 99%
“…Bicondylar tibial plateau fractures are complex injuries and treatment these fractures is challenging. Ideal method is still controversial with risk of unsatisfactory results ifnottreated properly [2]. Several strategies have been advocated for management of bicondylar tibial plateau fractures.…”
Section: Introductionmentioning
confidence: 99%